ANALYSIS OF ENTERPRISE ARCHITECTURE DESIGN FOR RISK AND QUALITY MANAGEMENT FUNCTION WITH TOGAF ADM (CASE STUDY: TELKOM CORPORATE UNIVERSITY CENTER) - Maulidya Ardini (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The rapid development of information technology affects how to do work that is digitized and prioritizes the use of technology. Alignment of information technology strategy with business is an important factor for a company or organization. However, not all companies can implement and develop information technology in accordance with company needs. One of them is the Telkom Corporate University Center (TCUC) Planning and Controlling unit in the Risk and Quality Management function. In the Risk & Quality Management function, there are obstacles in the operational function, namely having different applications for each business process which results in ineffectiveness. For this reason, Enterprise Architecture solutions are needed to overcome these problems. Enterprise Architecture is designed using the TOGAF (The Open Architecture Framework) framework with the ADM (Architecture Development Method) methodology. The design starts from the Preliminary Phase to the Migration Technology Architecture. The final result of this research is an Enterprise Architecture blueprint that can be implemented in the Risk and Quality Management Unit Planning and Controlling Telkom Corporate University Center (TCUC) function.